2021
DOI: 10.1177/14614448211034159
|View full text |Cite
|
Sign up to set email alerts
|

Polarized platforms? How partisanship shapes perceptions of “algorithmic news bias”

Abstract: The use of artificial intelligence-based algorithms for the curation of news content by social media platforms like Facebook and Twitter has upended the gatekeeping role long held by traditional news outlets. This has caused some US policymakers to argue that platforms are skewing news diets against them, and such claims are beginning to take hold among some voters. In a nationally representative survey experiment, we explore whether traditional models of media bias perceptions extend to beliefs about algorith… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 63 publications
0
10
0
2
Order By: Relevance
“…Interest in public engagement by scientists, and academic faculty more generally, is expanding across a range of disciplines as the scientific community becomes increasingly vocal about the necessity of public engagement with science [ 1 , 2 ]. Engagement is especially important when emerging issues such as COVID-19 [e.g., 3 ], human genome editing [e.g., 4 ], and artificial intelligence [e.g., 5 ] raise questions in public debate that cannot be answered solely by more scientific research.…”
Section: Introductionmentioning
confidence: 99%
“…Interest in public engagement by scientists, and academic faculty more generally, is expanding across a range of disciplines as the scientific community becomes increasingly vocal about the necessity of public engagement with science [ 1 , 2 ]. Engagement is especially important when emerging issues such as COVID-19 [e.g., 3 ], human genome editing [e.g., 4 ], and artificial intelligence [e.g., 5 ] raise questions in public debate that cannot be answered solely by more scientific research.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, we drew on a recent data set fielded by the authors' research group, Science Media and the Public (SCIMEP) [30].…”
Section: Secondary Data Analysesmentioning
confidence: 99%
“…For most, direct experience with AI comes through their cell phones and smart personal assistants, such as Alexa (Amazon) and Cortana (Microsoft Corporation), Siri (Apple), and Google Assistant (Google). A 2020 survey by the SCIMEP research group (n=2700) found that 83% of Americans used smartphones and 29% of Americans reported using smart personal assistants "at least once" to "a few times a week" [30].…”
Section: Knowledge Awareness and Experience With Ai In Generalmentioning
confidence: 99%
“…Son ya incontables las publicaciones académicas, working papers de grupos de investigación e investigaciones periodísticas que destacan el vasto poder infraestructural y de gatekeeping de las grandes tecnológicas, quienes gobiernan sobre la arquitectura tecnosocial de la red (Calice et al, 2021). Por citar algunos ejemplos, la mayor parte de las comunicaciones personales y profesionales online en el Estado español se llevan a cabo a través de alguna plataforma en propiedad de grandes corporaciones estadounidenses.…”
Section: Introductionunclassified